Rivaroxaban Underdose for Atrial Fibrillation with Stable Coronary Disease: The AFIRE Trial Findings - Arashi, Hiroyuki; Yamaguchi, Junichi; Hagiwara, Nobuhisa; Yasuda, Satoshi; Kaikita, Koichi; Akao, Masaharu; Ako, Junya; Matoba, Tetsuya; Nakamura, Masato; Miyauchi, Katsumi; Kimura, Kazuo; Hirayama, Atsushi; Matsui, Kunihiko; Ogawa, Hisao; on behalf of the AFIRE investigators (Thrombosis and Haemostasis, 2022)
Background Rivaroxaban monotherapy was noninferior to combination therapy (rivaroxaban plus antiplatelet therapy) in efficacy but superior in safety in the Atrial Fibrillation and Ischemic Events with Rivaroxaban in Patients with Stable Coronary Artery Disease (AFIRE) trial. Among 2,215 patients with atrial fibrillation (AF) and stable coronary artery disease (CAD), 1,378 had baseline creatinine clearance (CrCl) ≥50 mL/min and received 10 (underdose) or 15 mg/d (standard-dose) rivaroxaban. We aimed to assess the effects of rivaroxaban underdose on clinical outcomes.Methods We assessed efficacy endpoint (a composite of stroke, systemic embolism, myocardial infarction, unstable angina requiring revascularization, and death from any cause) and major bleeding in the subgroup of patients with preserved renal function in the AFIRE trial.Results Age ≥75 years, female sex, lower CrCl, heart failure, and percutaneous coronary intervention history were associated with the underdose prescription. The underdose group had a similar incidence of the efficacy endpoint (3.62 vs. 3.51% per patient-year; p = 0.871) and significantly lower incidence of major bleeding (0.82 vs. 2.17% per patient-year; p = 0.022) than the standard-dose group. In patients receiving monotherapy, the incidences of efficacy endpoint and major bleeding were similar between the groups, whereas in those receiving combination therapy, the incidence of major bleeding was significantly lower in the underdose group than that in the standard-dose group.Conclusion In patients with AF, stable CAD, and preserved renal function, rivaroxaban underdose was associated with similar rates of thrombotic events but a lower incidence of hemorrhagic events than the standard dose.Clinical Trial Registration AFIRE UMIN Clinical Trials Registry (https://www.umin.ac.jp/ctr/), number UMIN000016612, and ClinicalTrials.gov, number NCT02642419.
Keywords: coronary disease; direct oral anticoagulant; percutaneous coronary intervention; stent